Socioeconomic factors and outcomes from exercise-related sudden cardiac arrest in high school student-athletes in the USA. Issue 3 (29th October 2021) - Schattenkerk, Jared; Kucera, Kristen; Peterson, Danielle F; Huggins, Robert A; Drezner, Jonathan A
Abstract : Objective: Minority student-athletes have a lower survival rate from sudden cardiac arrest (SCA) than non-minority student-athletes. This study examined the relationship between high school indicators of socioeconomic status (SES) and survival in student-athletes with exercise-related SCA. Methods: High school student-athletes in the USA with exercise-related SCA on school campuses were prospectively identified from 1 July 2014 to 30 June 2018 by the National Center for Catastrophic Sports Injury Research. High school indicators of SES included the following: median household and family income, proportion of students on free/reduced lunch and percent minority students. Resuscitation details included witnessed arrest, presence of an athletic trainer, bystander cardiopulmonary resuscitation and use of an on-site automated external defibrillator (AED). The primary outcome was survival to hospital discharge. Differences in survival were analysed using risk ratios (RR) and univariate general log-binomial regression models. Results: Of 111 cases identified (mean age 15.8 years, 88% male, 49% white non-Hispanic), 75 (68%) survived. Minority student-athletes had a lower survival rate compared with white non-Hispanic student-athletes (51.1% vs 75.9%; RR 0.67, 95% CI 0.49 to 0.92). A non-significant monotonic increase in survival was observed with increasing median household or family income and with decreasing percent minority students or proportion on free/reduced lunch. The survival rate was 83% if an athletic trainer was on-site at the time of SCA and 85% if an on-site AED was used. Conclusions: Minority student-athletes with exercise-related SCA on high school campuses have lower survival rates than white non-Hispanic athletes, but this difference is not fully explained by SES markers of the school.